Mechanism of Action of Phenethyl Alcohol: Breakdown of the Cellular Permeability Barrier - Silver, Simon (1967)
Phenethyl alcohol (PEA) caused Escherichia coli to take up greatly increased amounts of acriflavine, a compound to which healthy growing cells are impermeable. PEA also caused an increased rate of efflux (leakage) of cellular potassium under conditions which do not greatly alter the influx of potassium via the energy-dependent potassium pump. We therefore propose that the primary effect of PEA is a limited breakdown of the cell membrane. The inhibition of deoxyribonucleic acid synthesis and other cellular functions would then be secondary consequences of the alteration in the membrane structure.